Odpowiedzi

2010-02-19T17:18:48+01:00
(a+b)*h:2 = pole1

(a+2+b+2)*3h:2 = nowe pole

( ah + bh ) :2 = pole1

(3ah + 3bh + 12h) :2 = pole nowe

pole nowe - pole1 =
=[(3ah + 3bh + 12h)-(ah + bh)] :2=
=(3ah + 3bh + 12h - ah - bh) :2 =
=(2ah + 2bh + 12h) :2 =
= ah + bh + 6h = h*(a+b+6) => o tyle się zwiększy pole
2 3 2
Najlepsza Odpowiedź!
2010-02-19T17:25:32+01:00
P=½(a+b)*h (wzór wyjściowy na obliczanie pola trapezu)

po zwiększeniu podstaw o 2, mamy:
a₁=a+2, b₁= b+2
wysokość 3 razy:
h₁=3h
P₁=½(a₁+b₁)*h₁
P₁=½(a+2+b+2)*3h
P₁=½(a+b+4)*3h

P₁-P=³/₂(a+b+4)*h-½(a+b)*h=³/₂ah+³/₂bh+³/₂*4h-½ah-½bh=
=³/₂ah-½ah+³/₂bh-½bh+6h=ah+bh+6h=(a+b+6)*h

2 3 2